Role of Immunohistochemistry in the Diagnosis of Sebaceous Carcinoma: A Clinicopathologic and Immunohistochemical Study. (November 2015) - Plaza, Jose A.; Mackinnon, Alexander; Carrillo, Luis; Prieto, Victor G.; Sangueza, Martin; Suster, Saul
Abstract : Abstract: Sebaceous carcinoma (SC) is a relatively uncommon malignant epithelial neoplasm with a predilection for the periocular region. The diagnosis of SC can be difficult to make at initial presentation, as it can clinically and histopathologically resemble other common benign and malignant epithelial lesions. A diagnosis of SC is made by confirmation of sebaceous differentiation of neoplastic cells, which can often be accomplished by conventional microscopic findings; however, its recognition may be sometimes difficult and requires ancillary studies such as immunohistochemistry (IHC). Many studies have evaluated the role of IHC as a potential technique to differentiate SC from its mimics; however, most of these studies have used a limited panel of antibodies with variable results. The aim of this study was to determine the efficacy of IHC in the diagnosis of SC and to provide some guidelines for interpretation in the diagnosis of these neoplasms. We studied 27 cases of SC with a broad panel of IHC markers using a tissue microarray technique. We also studied 21 control cases of basal cell carcinoma (BCC) and 22 control cases of squamous cell carcinoma (SCC). Representative tissue cores were taken and processed from each case, and the tissue microarrays were stained by standard methods using antibodies to EMA, CK7, Ber-EP4, Factor XIIIA, androgen receptor, p53, adipophilin, progesterone receptor membrane component 1 (PGRMC1), squalene synthase (SQS), and alpha/beta hydrolase domain-containing protein 5 (ABHD5). Our studies show that EMA was expressed in all cases of SC, CK7 was expressed in 24 of 27 cases, Ber-EP4 was expressed in 7 of 27 cases, Factor XIIIA was negative in all cases, androgen receptor was expressed in 9 of 27 cases, P53 was expressed in 12 of 27 cases, adipophilin was expressed in all cases, PGRMC1 was expressed in 22 of 27 cases, SQS was expressed in 11 of 27 cases, and ABHD5 was expressed in 9 of 27 cases. EMA was negative in all cases of BCC, CK7 was expressed in 6 of 21 cases, Ber-EP4 was expressed in 21 of 21 cases, Factor XIIIA was negative in all cases, androgen receptor was expressed in 3 of 21 cases, P53 was expressed in 4 of 21 cases, adipophilin, PGRMC1, SQS, and ABHD5 were negative in all cases of BCC. Similarly, EMA was expressed in 16 of 22 cases of SCC, CK7 was expressed in 2 of 22 cases, Ber-EP4, Factor XIIIA, and androgen receptor were negative in all cases, P53 was expressed in 3 of 22 cases, adipophilin, PGRMC1, SQS, and ABHD5 were negative in all cases of SCC. Our study indicates that adipophilin represents a sensitive and reliable marker for the diagnosis of SC and can be of help in separating this tumor from some of its mimics. Additionally, inclusion of various epithelial markers in the panel will be of help if adequately used. Other antibodies against the PAT family of lipid droplet-associated proteins including PGRMC1, SQS, and ABHD5 were not as sensitive as adipophilin for identifying sebaceous differentiation and may therefore not be as useful for differential diagnosis as adipophilin.